2016
DOI: 10.1007/s40808-016-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

On the stability and Hopf-bifurcation of a multi-delayed competitive population system affected by toxic substances with imprecise biological parameters

Abstract: In this paper we have analyzed the stability and Hopf-bifurcation behaviors of a multi-delayed two-species competitive system affected by toxic substances with imprecise biological parameters. We have exercised a method to handle these imprecise biological parameters by using parametric form of interval numbers. We have studied the feasibility of various equilibrium points and their stability. In case of toxic stimulatory system, the delay model exhibits a stable limit cycle oscillation due to variation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…At present, some literatures, such as [3,4,8,11,14,[16][17][18][19][22][23][24][25][26], have studied the effects of toxins on different ecosystem species. [4] indicated that once some external toxic substances directly infected the prey, then the predator consuming polluted prey was indirectly influenced by the toxicant.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some literatures, such as [3,4,8,11,14,[16][17][18][19][22][23][24][25][26], have studied the effects of toxins on different ecosystem species. [4] indicated that once some external toxic substances directly infected the prey, then the predator consuming polluted prey was indirectly influenced by the toxicant.…”
Section: Introductionmentioning
confidence: 99%
“…Hallam and Clark [6], Hallam et al [7], Hallam and De Luna [8] started eco-toxicological modeling through mathematics. In this context it is mentioned that De Luna and Hallam [13], Freedman and Shukla [5], Samanta [23], Shukla and Dubey [24] and others [10,17,21] have made important contributions on this field. However, most of these models recognize with single species or two-species ecological communities.…”
Section: Introductionmentioning
confidence: 99%
“…In recent time, mathematically modeling of eco-toxicological problems in aquatic environment are extensively studied by several researchers. They are paying attention on the eco-toxicological effects of toxic substances released by the marine biological species themselves [10,17,20,21,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e competition-cooperation relationship widely exists in the real enterprise clusters and has a major impact on the evolution of enterprise clusters [5][6][7][8][9]. To study the influence of competition and cooperation on the evolution of enterprise clusters, researchers propose a competition-cooperation enterprise cluster model [10] based on the ecology model [11][12][13][14][15], which is described as follows:…”
Section: Introductionmentioning
confidence: 99%